2020
DOI: 10.3390/w12092609
|View full text |Cite
|
Sign up to set email alerts
|

Re-Examination of the Relationship between Agricultural Economic Growth and Non-Point Source Pollution in China: Evidence from the Threshold Model of Financial Development

Abstract: The coordinated development of agricultural economic growth and non-point source (NPS) pollution is an important task in enhancing pollution prevention. Significantly, agricultural economic growth and NPS pollution are interrelated, and their mechanism will be affected by financial development. For this reason, the current study established a panel smooth transformation regression (PSTR) model to reveal the mechanical evolution under different financial development levels. It was found that the impact of agric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…The following abbreviations are used in this manuscript: NCER (Northeast Comprehensive Economic Region); NCCER (Northern Coastal Comprehensive Economic Region; ECCER (Eastern Coastal Comprehensive Economic Region); SCER (Southern Coastal Economic Region); YRCER (Yellow River Basin Comprehensive Economic Region); YRBCE (Yangtze River Basin Comprehensive Economic Region); GSCER (Great Southwest Comprehensive Economic Region); GNCER (Great Northwest Comprehensive Economic Region). Province numbers: Liaoning (6), Jilin (7), Heilongjiang (8), Beijing (1), Tianjin (2), Hebei (3), Shandong (15), Shanghai (9), Jiangsu (10), Zhejiang (11), Fujian (13), Guangdong (19), Hainan (21), Shaanxi (27), Shanxi (4), Henan (16), Inner Mongolia (5), Hubei (17), Hunan (18), Jiangxi (14), Anhui (12), Yunnan (25), Guizhou (24), Sichuan (23), Chongqing (22), Guangxi (20), Gansu (28), Qinghai (29), Ningxia (30), Tibet (26), Xinjiang (31).…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…The following abbreviations are used in this manuscript: NCER (Northeast Comprehensive Economic Region); NCCER (Northern Coastal Comprehensive Economic Region; ECCER (Eastern Coastal Comprehensive Economic Region); SCER (Southern Coastal Economic Region); YRCER (Yellow River Basin Comprehensive Economic Region); YRBCE (Yangtze River Basin Comprehensive Economic Region); GSCER (Great Southwest Comprehensive Economic Region); GNCER (Great Northwest Comprehensive Economic Region). Province numbers: Liaoning (6), Jilin (7), Heilongjiang (8), Beijing (1), Tianjin (2), Hebei (3), Shandong (15), Shanghai (9), Jiangsu (10), Zhejiang (11), Fujian (13), Guangdong (19), Hainan (21), Shaanxi (27), Shanxi (4), Henan (16), Inner Mongolia (5), Hubei (17), Hunan (18), Jiangxi (14), Anhui (12), Yunnan (25), Guizhou (24), Sichuan (23), Chongqing (22), Guangxi (20), Gansu (28), Qinghai (29), Ningxia (30), Tibet (26), Xinjiang (31).…”
Section: Fundingmentioning
confidence: 99%
“…As a comprehensive and systematic endeavor, agricultural green development encompasses a wide range of areas. Gaining a comprehensive and systematic understanding of the state of agricultural green development, is an important prerequisite and foundation for promoting its progress [7]. Measuring and analyzing the level of agricultural green development aids in monitoring and evaluating the environmental impact of agricultural activities while ensuring the sustainability of agricultural systems.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to achieve a harmonious development between environment, resources, and economic development, and the contradiction between the two is increasingly prominent. Based on the perspective of China's industrial development, since the 1980s, up to now, the growth rate of industrial wastewater discharge has shown a relatively low degree of decline [ 2 ]. However, in addition, the discharge of industrial solid pollutants and industrial waste gas both showed an increase, with an average increase of 6.36% and 8.49% per year, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The existing studies on farmland transfer have mainly focused on the relationship between farmland transfer and economic and environmental variables, such as household income [13], poverty vulnerability [14], allocation efficiency of agricultural land [15], and environmental performance [16][17][18]. Li et al (2019) [13] used fuzzy mathematical methods to estimate the welfare gap before and after farmland transfer in Guangzhou, Wuxi, and Chongqing, finding that the overall welfare of farmers after farmland transfer increased by 17.5%, 15.1%, and 23.5%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, some scholars put forward the opposite view. Jiang et al (2021) [18] point out that moderatescale operations did not meet the policy expectation of curbing agricultural nonpoint source pollution; [20] also found that farmland transfer improved the overall nonpoint source pollution level of the transferred farmland.…”
Section: Introductionmentioning
confidence: 99%